Red Light Regulates the Metabolite Biosynthesis in the Leaves of “Huangjinya” Through Amino Acid and Phenylpropanoid Metabolisms - Ma, Qingping; Song, Laichao; Niu, Zhanhai; Li, Jingshan; Wang, Yu; Sun, Haiwei; Ren, Zhihong; Zhao, Hongxia; Guo, Shangjing; Ding, Zhaotang (Frontiers in Plant Science, 2022)
‘Huangjinya’ is a light sensitive albino variety and widely cultivated in China. It has been proved that red light could promote the vegetable growth of plants. However, the mechanism of ‘Huangjinya’ in response to red light is unclear. This study used high-throughput sequencing technology to analyze the transcriptome of tender shoots of ‘Huangjinya’ under white and red light supplement conditions. At the same time, LC-MS was used to analyze metabolite changes under different light conditions. Transcriptome analysis revealed that a total of 174 differential expressed genes (DEGs) were identified after red light supplement. KEGG classification indicated that amino acid metabolism enriched the most DEGs. In addition, two phenylpropanoid metabolism related genes and five CsGSTs were found to be expressed differently. Metabolome analysis revealed that 193 differential metabolites were obtained. Being the same as transcriptome analysis, most differential metabolites were enriched in amino acids, sweet and umami tasting amino acids were increased and bitter tasting amino acids were decreased after red light supplement. In summary, red light supplementary treatment may be propitious to the quality of ‘Huangjinya’ due to its regulatory effect on amino acid metabolism. As well, CsGSTs involved phenylpropanoid metabolism contributed to tea quality changes of ‘Huangjinya’.